NITRATES AND PHOSPHATES CONTENT IN THE WATER AND SEDIMENT IN SEAGRASS ECOSYSTEM IN THE NORTH OF COASTAL AREA OF RUPAT SUB DISTRIC BENGKALIS RIAU - Sitorus, Tiroy; ', Zulkifli; ', Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was take place in north Rupat island beach, Bengkalis regency Riau province on January 2016. The purpose of this research is to find out the contents of nitrate and phosphate in the water of seagrass ecosystem in north Rupat island and to find out the contents of nitrate and phosphate in the sediment of seagrass ecosystem in north Rupat island as well as to find out the difference of nitrate and phosphate contents in the water and sediment between station. The parameter that have been observed is the physics and chemist of water parameter. Transect squares device was use to calculated the density. While to determine nitrate and phosphate in the water leads to Saeni and Latifah in Sanggam, 2008 and to determine nitrate and phosphate in sediment leads to Siaka et al., 1998. Base on research result the average content of nitrate in the water is 0.2264-0.2417 mg/L, and in the sediment 0.1347-0,.5319 mg/L. While the average content of phosphate in the water was 0.1991-0.2433 mg/L, and in the sediment 0.2507-0.3872 mg/L. The density of seagrass on each station in north Rupat island beach was about 23.66-154.66 stands/m2. From the result of this research we found from the t test result, the significant differences of content of nitrate and phosphate in water an cediment show that the differences is not significant, show that the condition of north coatsal of Rupat island is water that has midlle level of pressure and polution.Keywords: density of seagrass, Nitrate, Phosphate, Water, Sediment, Seagrass Ecosystems, North Shore Rupat Island, Riau Province